(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2020)
The growth and development of the nestlings of white-throated kingfisher (Halcyon smyrnensis) showed that at the hatching day, the mean body weight was 14.6±1.0 g which gained up to 69.9±3.0 g during fledging. The mean length of the body, wing, beak, head, tarsus and feet were 59.4±12.4, 19.4±5.7, 3.1±1.2, 11.7±1.4, 8.5±1.8 and 17.3±3.6 mm, respectively at the hatching day and 203.5±14.1, 105.7±5.8, 40.4±1.3, 29.1±1.1, 14.9±0.4 and 29.8±0.7 mm, respectively during fledging day. The primaries, rectrices and the claw was started to grow from 3rd day hatching and grew up to 67.8±5.6, 27.7±3.4 and 5.2±0.2 mm, respectively during fledging time. J. Asiat. Soc. Bangladesh, Sci. 46(1): 71-80, June 2020